Affective Responses From Different Modalities of Resistance Exercise: Timing Matters! - Cavarretta, Daniel J.; Hall, Eric E.; Bixby, Walter R. (Frontiers in Sports and Active Living, 2019)
Resistance exercise provides positive changes in affect that may increase adherence. Little is known about the temporal dynamics of affect or the relationship between training modality and affect. This experiment investigated the temporal dynamics of affect during resistance exercise and compared the affective responses from machine and free weight exercises. Twenty-eight novice lifters (21 females) completed 2 workouts consisting of 4 machine or 4 free weight exercises for 3 sets of 9–11 repetitions at 80% 10 repetition-maximum. Feeling Scale was administered at baseline, during, 5- and 30-min post. During the workout, Feeling Scale was administered during the seventh repetition of the second set and after completion of the third set to provide an intra- and inter-set affective measurement. A Repeated Measures General Linear Model revealed a significant effect for time (p < 0.001) with affect more positive for all time points, 5- and 30-min following exercise compared to baseline levels (p's < 0.001). Additionally, affect was more positive at 5- compared to 30-min post (p = 0.015) and higher for the inter-set measurement compared to the intra-set measurement (p = 0.001). The results suggest that affective valence becomes more positive during and following resistance exercise. This preliminary evidence suggests affective rebounding may occur after cessation of the set. Lastly, there appears to be no differences in the affective responses from machine and free weight exercises among novice lifters although this finding may be confounded by other factors such as differences in muscle group selection or total amount of volume performed.